Effects of Low-Dose-Gamma Rays on the Immune System of Different Animal Models of Disease - Noriko Shimura; Shuji Kojima (SAGE Publishing, 2014)
We reviewed the beneficial or harmful effects of low-dose ionizing radiation on several diseases based on a search of the literature. The attenuation of autoimmune manifestations in animal disease models irradiated with low-dose γ-rays was previously reported by several research groups, whereas the exacerbation of allergic manifestations was described by others. Based on a detailed examination of the literature, we divided animal disease models into two groups: one group consisting of collagen-induced arthritis (CIA), experimental encephalomyelitis (EAE), and systemic lupus erythematosus, the pathologies of which were attenuated by low-dose irradiation, and another group consisting of atopic dermatitis, asthma, and Hashimoto's thyroiditis, the pathologies of which were exacerbated by low-dose irradiation. The same biological indicators, such as cytokine levels and T-cell subpopulations, were examined in these studies. Low-dose irradiation reduced interferon (IFN)-gamma (γ) and interleukin (IL)-6 levels and increased IL-5 levels and the percentage of CD4 + CD25 + Foxp3 + Treg cells in almost all immunological disease cases examined. Variations in these biological indicators were attributed to the attenuation or exacerbation of the disease's manifestation. We concluded that autoimmune diseases caused by autoantibodies were attenuated by low-dose irradiation, whereas diseases caused by antibodies against external antigens, such as atopic dermatitis, were exacerbated.